2008
DOI: 10.1139/y08-031
|View full text |Cite
|
Sign up to set email alerts
|

DOCA-salt treatment enhances responses to endothelin-1 in murine corpus cavernosumThis article is one of a selection of papers published in the special issue (part 1 of 2) on Forefronts in Endothelin.

Abstract: The penis is kept in the flaccid state mainly via a tonic activity of norepinephrine and endothelins (ETs). ET-1 is important in salt-sensitive forms of hypertension. We hypothesized that cavernosal responses to ET-1 are enhanced in deoxycorticosterone acetate (DOCA)-salt mice and that blockade 1 This article is one of a selection of papers published in the special issue (part 1 of 2) on Forefronts in Endothelin.2Corresponding author (e-mail: E-mail: fcarneiro@mcg.edu). NIH Public Access

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…49 Moreover, the DOCA/salt hypertension model exhibits increased caspase-1 and IL-1β activity in the kidney, 50 and it is characterized by ET-1 overexpression. 6,51 As observed in the present study, ET-1 does not need previous stimulation with LPS to increase pro-caspase-1 and pro-IL-1β, and the increased caspase-1 and IL-1β are in agreement with direct stimulation of NF-κB.…”
Section: Discussionsupporting
confidence: 86%
“…49 Moreover, the DOCA/salt hypertension model exhibits increased caspase-1 and IL-1β activity in the kidney, 50 and it is characterized by ET-1 overexpression. 6,51 As observed in the present study, ET-1 does not need previous stimulation with LPS to increase pro-caspase-1 and pro-IL-1β, and the increased caspase-1 and IL-1β are in agreement with direct stimulation of NF-κB.…”
Section: Discussionsupporting
confidence: 86%
“…Penile VSM cells are able to synthesize ET-1 as well as respond to stimulation with ET-1(18). In addition, both ET-A and ET-B have been reported to be expressed in cavernosal tissue (1922). In the penis, ET-1 induces corpus cavernosum vasoconstriction through the ET A receptor and subsequent activation of the inositol triphosphate (IP 3 ) / Ca 2+ signaling pathway (Ca 2+ sensitive) and the RhoA/Rho-kinase signaling pathway (Ca 2+ independent) (23).…”
Section: C- Ed In Hypertensionmentioning
confidence: 99%
“…Concurrently, ET-1 was shown to increase ROS generation via NADPH oxidase activation. Data from our laboratory has shown that ET-1 mediates not only penile vasoconstriction, but also contraction of the internal pudendal artery, the major artery providing blood flow to the penis (22, 25). We have also revealed that the corpora cavernosum from DOCA-salt hypertensive rats exhibit increased contractile responses to ET-1when compared with their normotensive counterpart controls (22).…”
Section: C- Ed In Hypertensionmentioning
confidence: 99%
“…In the vasculature, ET-1 elicits reactive oxygen species (ROS), production by NADPH oxidase enzyme, which in turn releases ET-1, favouring a prohypertensive [ 158 , 159 ]. Animal model studies reveal ET-1 to be essential in salt-sensitive hypertension-related ED [ 160 , 161 ]. Furthermore, ET-1 generated Ca 2+ influx alteration, prompting smooth muscle contraction in isolated penile tissue [ 162 ].…”
Section: Gender Differences In Et-1 Functionalitymentioning
confidence: 99%